OPTIMALISASI PEMANFAATAN DANA DESA DI TEMPIRAI SELATAN KABUPATEN PALI - Maria, Maria; Indriasari, Desi; Sari, Karika Rachma; Utami, Agnes; Alfarishi, Ahmad Fauzan; Rianto (Jurusan Akuntansi Politeknik Negeri Sriwijaya Palembang, 2025)
This activity aims to increase the capability and capacity of village government officials in solving problems is the participatory method. The location of the activity was in South Tempirai Village, North Penukal District, Pali Regency. This activity involves the village head and his apparatus. Efforts to utilize village funds are carried out by reviving the formation of BUMDesa However, in its implementation there are several obstacles, including differences in paradigms from stakeholders regarding the management of village funds, lack of community participation in implementing the BUMDesa work program. The solution provided is counseling about increasing the competency of BUMDes managers, starting from strategic planning, programming, budgeting, implementation and the importance of BUMDesa financial management. It is hoped that from the results of the activity, the South Tempirai village government, especially village officials, can develop BUMDesa and accommodate the fulfillment of community needs through the potential of local wisdom.